The patient journey with NMOSD: From initial diagnosis to chronic condition - Delgado-Garcia, Guillermo; Lapidus, Sheryl; Talero, Rosa; Levy, Michael (Frontiers in Neurology, 2022)
Objective: To better understand the patient experience with neuromyelitis optica spectrum disorder (NMOSD) through the course of the illness. Background: NMOSD is a rare autoimmune disorder that causes recurrent inflammatory attacks of the optic nerve, spinal cord, and brain. Knowledge and awareness of NMOSD in the general medical community are often limited, resulting in potential delays in diagnosis and treatment. Design/Methods: We developed a comprehensive 101-question survey to understand the patient’s perspective on their journey from initial presentation to present condition. The survey covered basic demographics, symptoms, medical tests used to reach a diagnosis, and the patient’s psychosocial responses to their diagnosis. The survey included questions to determine internal consistency in responses. We shared the survey with members of the Neuromyelitis Optica (NMO) Clinic Facebook group and received responses from 151 patients. All data collected were self-reported and presented as summary statistics. Results: The majority of survey responses were from patients who were female (83%) and White (76%), Asian (7%), or African American (7%). Initial symptoms of disease included fatigue, pain, stiffness/spasticity, bladder and bowel dysfunction, cognitive/emotional symptoms, and visual disturbances. Initial reactions to NMOSD diagnosis were frequently fear, anxiety, and/or depression. Mean (SD) time to diagnosis was 2.2 (3.2) years. First contact with a medical professional was felt to be not helpful or somewhat helpful for many patients (71%), in part due to uncertain diagnosis and/or treatment. However, once referred to specialists (primarily neurologists), the majority of patients (87%) reported finding a professional who could help. Tests leading to diagnosis included magnetic resonance imaging, lumbar puncture, and blood tests for autoantibodies including aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG). While approximately 30% of patients still felt challenged for a variety of reasons, most patients reported that having a diagnosis and being under the care of a specialist contributed to a comprehensive plan with hope for their future. Conclusions: The NMOSD patient journey frequently begins with anxiety, fear, and frustration. Finding the right specialist and identifying appropriate screening tests can lead to earlier diagnosis and progression toward better patient outcomes.